Transcultural graffiti : diasporic writing and the teaching of literary studies - West-Pavlov, Russell (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft, 2005)
Transcultural Graffiti reads a range of texts - prose, poetry, drama - in several European languages as exemplars of diasporic writing. The book scrutinizes contemporary transcultural literary creation for the manner in which it gives hints about the teaching of literary studies in our postcolonial, globalizing era. Transcultural Graffiti suggest that cultural work, in particular transcultural work, assembles and collates material from various cultures in their moment of meeting. The teaching of such cultural collage in the classroom should equip students with the means to reflect upon and eng.